Analysis and evaluation of mobile rhythm games : Game structure and playability - Doo Heon Song; Kwang Baek Kim; Jong Hee Lee (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The rhythm game is an action simulation game adapted to the presented music. While it is expected to have an educational effect as a functional game, the relationship between the operability and rhythm education under the mobile platform is still questionable. In Korea, it seems that mobile rhythm game is a minority maniac genre that are played mostly among teenagers and early twenties. In this paper, we select three mobile rhythm games that are most played by Korean gamers in analysis. First, we analyze the user interface layout, note control, evaluation style and level of difficulty for three games – Deeno, Cytus, and Lanota. Then, we take a user survey in order to evaluate the playability of those games. All three games obtain high scores but there exust several statistically significant differences among games in analysis.